183k views
19 votes
Evaluate −nz−z2−2z when n=3. Simplify your answer.

2 Answers

6 votes

Answer: n=

−z2−5

z

Explanation:

Let's solve for n.

(−n)(z)−z2−2=3

Step 1: Add z^2 to both sides.

−nz−z2−2+z2=3+z2

−nz−2=z2+3

Step 2: Add 2 to both sides.

−nz−2+2=z2+3+2

−nz=z2+5

Step 3: Divide both sides by -z.

−nz

−z

=

z2+5

−z

User Manwithfewneeds
by
5.4k points
6 votes

Answer:

-z^2-5z

Explanation:

To evaluate a polynomial at a given value, we substitute the given value for the variable and then simplify using order of operations. We are given n=3, so we substitute 3 for n in the polynomial −nz−z2−2z and simplify as follows.

−nz−z2−2z

−(3)z−z2−2z

−3z−z2−2z

−z2−5z

User Deepak Mallah
by
4.9k points